Modern Approaches in the Morphological Diagnosis of Inflammatory Bowel Diseases - A. S. Tertychnyy; Kh. M. Akhriyeva; E. A. Kogan; O. V. Zayratyants; L. S. Selivanova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The purpose of the review: to summarize the main data of the literature and our own accumulated practical experience of everyday diagnosis of inflammatory bowel diseases (IBD) to better represent the morphological features and histological conclusions.Key points. The microscopic picture of IBD is often represented by a combination of basic histological characteristics that can be detected in other diseases and only in rare cases can be considered pathognomonic. No single histological feature can be used in isolation to diagnose ulcerative colitis or Crohn’s disease. Diagnostic accuracy is improved if several signs are taken into account at once, if changes within one or more parts of the intestine are analyzed, it is necessary to compare the identified changes with the clinical picture of the disease.Conclusion. The presented stages of the morphological study of biopsy specimens in patients with IBD and the exact characteristics of the detected changes will help to increase the diagnostic value of the study of ileo- and colonobiopsies, as well as improve mutual understanding between gastroenterologists and pathologists and, as a result of interaction between specialists, will increase the accuracy of the diagnosis.